Cost-utility analysis of R-CHOP vs CHOP in patients with non-hodgkin's lymphoma: a systematic review - Cadag, Camille Francesca T.; Lorenzo, Althea B.; Mercado, Justine Marie M.; Ngo, Frances Lois U. (Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2024)
Background: Non-Hodgkin Lymphoma (NHL) ranks 11th in cancer incidence and mortality in the Philippines with the combination chemotherapy composed of Cyclophosphamide, Doxorubicin, Vincristine, and Prednisone (CHOP) being commonly used as treatment. However, the addition of Rituximab to CHOP (R-CHOP) has been shown to exhibit higher response rates and longer remissions, potentially improving quality of life. Currently, there is conflicting evidence on the cost-utility of CHOP versus R-CHOP.

Objective: The study aimed to describe the patient- and country-specific factors, and treatment modalities used for NHL and systematically review cost-utility evidence of R-CHOP versus CHOP in adult NHL patients.

Methodology: A systematic literature search of cost-utility studies on R-CHOP versus CHOP for NHL treatment was performed on eight databases: PubMed/MEDLINE, Scopus, Web of Science, EBSCOHost, Cochrane, York Research Database, Centre for Reviews and Dissemination Database, and HERDIN, where 607 studies were identified. Upon screening using an eligibility criteria, 10 studies were included and critically assessed using four appraisal tools: CHEERS, Drummond, Cooper, and ECOBIAS. These were performed independently by two authors with a third author assisting to help reach a consensus.

Results: All studies from HICs (n=8) and LMIC (n=1) suggested that R-CHOP was more cost-effective for NHL treatment than CHOP in terms of utility outcomes. The study conducted in an LIC (n=1) suggested the opposite, favoring CHOP over R-CHOP. Methodological differences such as perspective, discount rate, WTP, time horizon, and economic model were observed. Methodological limitations include completeness of data reported and credibility of sources used.

Conclusion & Recommendation: The results of this review shall be interpreted with caution as those favoring R-CHOP over CHOP for NHL treatment in terms of cost-utility were concentrated in HICs. More economic evaluations from LICs, LMICs, and UMICs are needed for a robust conclusion. Additionally, establishing a universally-recognized guideline for economic evaluations is essential to guide researchers effectively.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, June 2024
Keywords: Cost effectiveness -- Lymphoma--therapy -- Comparative effectiveness research; Non-Hodgkin’s Lymphoma, .; R-CHOP.; CHOP; Rituximab; Cost-utility.; Economic evaluation